Intergenerational transmission of trauma and family systems theory: an empirical investigation. Issue 3 (7th July 2020) - Fitzgerald, Michael; London‐Johnson, Antoinette; Gallus, Kami L.
Abstract : Research indicates that intergenerational transmission of trauma often leads to behavioural and emotional problems in children of parents with a history of trauma; however, intervening pathways are less well understood. The current study used the Longitudinal Studies of Child Abuse and Neglect (LONGSCAN; Runyan et al., 1998) data set. Among a sample of 361 mothers involved with child welfare services or 'at risk' of becoming involved in the future, we explored harsh parenting and couple relationship quality as mechanisms in the transmission of maternal trauma to changes in children's behavioural and emotional problems over a two‐year period. Findings indicate that verbal aggression predicted children's internalising and externalising issues, but negative relationship quality was the only significant mechanism linking maternal trauma to children's mental health problems. Clinical implications are discussed. Practitioner points: Trauma has a twofold effect on women's romantic relationships, increasing negative qualities and decreasing positive qualities Providing a trauma‐informed approach to therapy with a focus on the negative relationship quality can reduce harsh parenting and a child's internalising symptomology 抽象: 创伤的代际传递与家庭系统理论：实证研究: 研究表明，创伤的代际传递通常会导致有创伤史父母的子女出现行为和情绪问题；然而，干预途径还不太清楚。本研究使用了儿童虐待与忽视纵向研究（LONGSCAN; Runyan et al., 1998）的数据。在361名已参与儿童福利服务或未来"有可能"参与的母亲中，我们探索了在两年的过程中，严苛教养和夫妻关系质量是如何成为母亲创伤与儿童行为和情绪问题变化之间的传播机制。研究结果表明，言语攻击可以预测儿童的内化和外化问题，但负面关系质量是母亲创伤与儿童心理健康问题之间唯一显著的联系机制。本文讨论了其临床意义。 对从业者的启示: 创伤对女性的恋爱关系有双重影响，即增加消极品质与减少积极品质 提供创伤指引的治疗方法，重点关注负面关系质量，可以减少严苛教养和孩子的内化症状 Resumen: Transmisión intergeneracional del trauma y teoría de los sistemas familiares: una investigación empírica: La investigación indica que la transmisión intergeneracional del trauma a menudo conduce a problemas conductuales y emocionales en los hijos de padres con antecedentes de trauma; sin embargo, la trayectoria de esa influencia es menos conocida. El presente estudio utilizó el conjunto de datos Longitudinal Studies of Child Abuse and Neglect (LONGSCAN; Runyan et al., 1998). Entre una muestra de 361 madres atendidas por los servicios de bienestar infantil o 'en riesgo' de necesitar dichos servicios, exploramos la dureza de la crianza y la calidad de la relación de pareja como mecanismos en la transmisión del trauma materno a los cambios evidenciados en problemas conductuales y emocionales de los niños durante un periodo de dos años. Los resultados indican que la existencia de agresión verbal predice los problemas de internalización y externalización de los niños, pero la calidad negativa de la relación fue el único mecanismo significativo que vinculaba el trauma materno con los problemas de salud mental de los niños. Se discuten las implicaciones clínicas. Puntos de implicación práctica: El trauma tiene un doble efecto en las relaciones románticas de las mujeres, aumentando cualidades negativas y disminuyendo cualidades positivas de esas relaciones Proporcionar un enfoque de la terapia basado en el trauma con un enfoque en la calidad negativa de la relación puede reducir la crianza severa y la sintomatología internalizante de un niño